Nepal’s quest for Universal Health Coverage - Mishra, Shiva Raj; Khanal, Pratik; Dhimal, Meghnath (Journal of Pharmacy Practice and Community Medicine)
Universal Health Coverage (UHC) is one of the 13 targets under the third goal of Sustainable Development Goals (SDGs).[1] While the progress towards UHC in many Low and Middle Income Countries (LMICs) has often been feeble due to inadequate fiscal capacity, lack of governance structures and political commitment, the Himalayan nation Nepal is making some progress. The National Health Policy 2014 and National Health Insurance Policy 2013 of Nepal have UHC as one of the policy strategies. However, Nepal’s quest for UHC is fraught with many challenges.